Teste de condutividade elétrica para sementes de milho e de soja armazenadas sob baixa temperatura - Rosa, Mariana Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Electrical conductivity test is recommended to evaluate vigor of pea seeds and suggested for soybean. However, some cares must be taken for this test, when conducted for seeds stored at low temperature. Thus, the present work was carried out in order to verify if the use of rest time at higher temperature of seeds before the imbibitions for the electrical conductivity test can increase the viability of the test for maize and soybean seeds, stored at 10 °C. Five seed lots for each species, with similar germination levels were used. After the initial evaluations, soybean seed lots were stored during 15 months and maize seed lots during 16 months at low temperature. The laboratory analysis (seed moisture content; germination and vigor: accelerated aging; cold and electrical conductivity tests) were performed initially and repeated periodically after the storage (10 °C and 60% of air relative humidity) at 3, 6, 9, 12 and 15 months for soybean and 4, 8, 12 and 16 months for maize. Since the second evaluation for both species a new variable was added to the electrical conductivity test, denominated rest time of the seeds, used between the removal of the seeds of the cold chamber and the start of the imbibition for the conductivity test. The rest time periods of 0, 6, 12 and 24 hours were used, at two temperatures, 20 e 25 to 30 °C, aimed to verify, in this way, the effect of these periods and temperatures on the results of the electrical conductivity throughout of the storage period at low temperature.

O teste de condutividade elétrica é recomendado para avaliar o vigor de sementes de ervilha e é sugerido para soja. Entretanto, alguns cuidados devem ser adotados para esse teste, quando conduzido para sementes armazenadas sob condições de baixa temperatura. Assim, o presente trabalho teve como objetivo verificar se a utilização de períodos de repouso de sementes em temperaturas mais altas antes da embebição no teste de condutividade elétrica elevaria a viabilidade do teste para sementes de milho e soja, armazenadas a 10 °C. Foram utilizados cinco lotes de sementes para cada espécie, com germinação semelhante. Após as avaliações iniciais, os lotes de soja foram armazenados por 15 meses e os de milho por 16 meses sob baixa temperatura. Desse modo, foram realizadas análises laboratoriais preliminares (teor de água; germinação e vigor: envelhecimento acelerado; teste de frio e condutividade elétrica), repetidas periodicamente após o armazenamento em câmara a 10 °C e 60% de umidade relativa aos 3, 6, 9, 12 e 15 meses para soja e aos 4, 8, 12 e 16 meses para milho. A partir da segunda época de avaliação para ambas as espécies foi inserida nova variável ao teste de condutividade elétrica, denominada período de repouso das sementes, utilizada entre a remoção das sementes da câmara fria e o início da embebição.
Keywords: Sementes - Armazenamento; Sementes - Deterioração; Soja; Milho; Repouso de sementes; Vigor; Glycine max; Zea mays; Seed storage; Vigour; deterioration; Rest time of seeds